2022
DOI: 10.1037/ocp0000311
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the individual: A systematic review of the effects of unit-level demands and resources on employee productivity, health, and well-being.

Abstract: Creating sustainable employment—that is, a condition in which employees remain productive but also enjoy good health and well-being—is a challenge for many organizations. Work environment factors are major contributors to these employee outcomes. The job demands–resources model categorizes work environment factors into demands versus resources, which are, respectively, detrimental versus beneficial to employee outcomes. Although conceptualized as workplace factors, these job characteristics have been studied m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 74 publications
(141 reference statements)
1
24
1
1
Order By: Relevance
“…Qualitative reviews require an in-depth understanding of articles; as such, we excluded studies that were published in languages other than English. While this approach is consistent with both quantitative and qualitative review studies (e.g., Park & Martinez, 2022; Roczniewska et al, 2022), we acknowledge that it might lead to omitted samples. Second, as evident from our review, there is a high level of heterogeneity among studies in terms of their different operationalizations of work breaks.…”
Section: Review Limitationssupporting
confidence: 56%
“…Qualitative reviews require an in-depth understanding of articles; as such, we excluded studies that were published in languages other than English. While this approach is consistent with both quantitative and qualitative review studies (e.g., Park & Martinez, 2022; Roczniewska et al, 2022), we acknowledge that it might lead to omitted samples. Second, as evident from our review, there is a high level of heterogeneity among studies in terms of their different operationalizations of work breaks.…”
Section: Review Limitationssupporting
confidence: 56%
“…9 Forms of organizational support likely to benefit all students include training faculty and administrators in follower-supportive leadership behaviors, increasing opportunities for faculty and peer social support, building social capital (eg, transparency and fairness in school policies, student voice in organizational decisions), and providing students with greater autonomy in their learning. 10 Students of color are likely to derive additional benefit from an organizational climate of belonging and increased diversity among faculty and staff, as they are more likely to seek support from people who have faced similar experiences on account of their race. 8 Wellness behaviors tended to decrease over time, but these trends did not correspond to decreases in resilience.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, decrease in job satisfaction also results in lower employee performance. Confirmation for this mechanism explaining the phenomenon in JD-R theory in question was presented by Roczniewska et al (2022). Based on a systematic review of existing studies, they showed that escalating demands not only result in negative effects on strain, but there is a reduction in job satisfaction that leads to a reduction in employee performance (in-role and extra-role behaviours).…”
Section: Politics In Organisationsmentioning
confidence: 93%